2010
DOI: 10.12968/jowc.2010.19.5.48046
|View full text |Cite
|
Sign up to set email alerts
|

Cost of wound treatment to increase significantly in Denmark over the next decade

Abstract: Wound therapy will pose a major economic challenge to Denmark in future if no intervention is carried out. This study presents an empirical model calculating the economic consequences of future challenges such as demography, lifestyle and type 2 diabetes mellitus. It is suggested that a national strategy for wound therapy may convert a future deficit to zero-balance. Similar challenges are expected in other western European countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 6 publications
0
29
0
1
Order By: Relevance
“…For example, a cost modelling conducted in Australia suggested that the three most common chronic wounds (pressure injuries, foot wounds associated with diabetes and leg ulcers) present a cost of US$2·85 billion per annum across hospital, community and residential aged care settings. A cost modelling study conducted in Denmark suggested that chronic wounds cost DKK56m (€8 m) in 2009, and this cost will increase to DKK224m (€30 m) in the year 2020 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, a cost modelling conducted in Australia suggested that the three most common chronic wounds (pressure injuries, foot wounds associated with diabetes and leg ulcers) present a cost of US$2·85 billion per annum across hospital, community and residential aged care settings. A cost modelling study conducted in Denmark suggested that chronic wounds cost DKK56m (€8 m) in 2009, and this cost will increase to DKK224m (€30 m) in the year 2020 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, existing evidence point in the direction that more specialised and intense wound care is cost-effective and not rarely cost-saving [23]. Moreover, a Danish study has argued that by adopting a national strategy based on best practice guidelines, it may be possible to reduce the costs for wound management with up to 30% [24]. …”
Section: Introductionmentioning
confidence: 99%
“…6 The annual wound care costs in Denmark, a country with similar demographics to that of Finland, are estimated to be around 100 million euros. 7 From the perspective of patients, community, and health-care resources, a new, safe, clinically-and cost-effective method for the treatment of chronic wounds would be undoubtedly welcome.…”
Section: Scope and Significancementioning
confidence: 99%